Intra-population strain variation in phosphorus storage strategies of the freshwater cyanobacterium Raphidiopsis raciborskii. Issue 6 (14th May 2020) - Xiao, Man; Hamilton, David P; Chuang, Ann; Burford, Michele A
ABSTRACT: Several cyanobacteria, including diazotrophic Raphidiopsis raciborskii, can form harmful blooms when dissolved inorganic phosphorus concentrations are very low. We hypothesized that R. raciborskii strains would vary in phosphorus (P) allocations to cell growth and storage, providing resilience of populations to continuously low or variable P supplies. We tested this hypothesis using six toxic strains (producing cylindrospermopsins) isolated from a field population using batch monocultures with and without P and dissolved inorganic nitrogen (DIN). Treatments replete with DIN, irrespective of P addition, had similar exponential growth rates for individual strains. P storage capacity varied 4-fold among strains and was significantly higher in DIN-free treatments than in replete treatments. P was stored by all R. raciborskii strains, in preference to allocation to increase growth rates. P stores decreased with increased growth rate across strains, but weeere not related to the time to P starvation in P-free treatments. The storage capacity of R. raciborskii, combined with strategies to efficiently uptake P, means that P controls may not control R. raciborskii populations in the short term. Intra-population strain variation in P storage capacity will need to be reflected in process-based models to predict blooms of R. raciborskii and other cyanobacteria adapted to low-P conditions. Abstract : Strains of the cyanobacterial species Raphidiopsis raciborskii preferentially stored phosphorus over growth allocation to confer a longer growth period and support population persistence.